Mentoring Dynamics: Medical Student’s Perspectives in a Private Medical College Setting - Dr. Sadaf Sajid; Dr Syma Arshad; Azqa Ali; Dr Umera Saleem; Dr. Anwar. Ul Haq, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Mentoring in medical education is an evolving strategy to support students’ academic, personal, and professional development. In Pakistan, structured mentoring programs are still limited, and students face diverse academic, emotional, and social challenges during medical training. Understanding their perceptions can inform the improvement of such initiatives. Objective: To evaluate medical students’ perceptions of mentoring with respect to academic support, personal development, emotional and psychological support, and to compare perceptions between pre-clinical and clinical years as well as between genders. Methods: A cross-sectional study was conducted at Rashid Latif Medical College, Lahore, after one year of implementing a formal mentorship program. Using a validated questionnaire (Cronbach’s α = 0.67; item range 0.62–0.93), data were collected from 300 MBBS students (150 pre-clinical; 150 clinical) through universal sampling. Responses were recorded on a five-point Likert scale. Independent sample t-tests were applied to compare mentoring domains across academic years and gender. Results: Among participants (53.7% females, 44.7% males), most reported positive perceptions toward mentoring (pre-clinical: 45.3–54.6%; clinical: 45.6–63.8%). Academic support was the most highly endorsed domain (46.6–68.7% pre-clinical; 50.6–75.4% clinical), particularly in receiving constructive feedback. Personal development was positively perceived by 25.4–64.7% (pre-clinical) and 34–60% (clinical), while emotional/psychological support was endorsed by 34–74.6% and 26–69%, respectively. No statistically significant difference was observed between pre-clinical and clinical students across domains (p>0.05). Gender comparison showed significant difference only in academic support (p<0.05), with females reporting greater benefit. Conclusion: Medical students generally perceived mentoring positively, especially regarding academic support. While no difference existed between academic years, female students benefited more in terms of academic support. Formal mentoring programs should be expanded in Pakistani medical colleges, with greater emphasis on personal, emotional, and career-related guidance.